PROVENANCE AND SOURCE OF METATERRIGENOUS ROCKS OF THE LADOGA GROUP: RESULTS OF GEOCHEMICAL AND SM-ND ISOTOPE-GEOCHEMICAL STUDY - Kotova L.N.; Glebovitsky V.A.; Kotov A.B.; Podkovyrov V.N.; Savatenkov V.M. (My University, 2006)
The Ladoga Group makes up a significant part of the northern Ladoga region. This group represents the Kalevian stratotype of the Karelian region and is considered an analogue of the Kalevian terrigenous rocks of Finland. Systematic geochemical and isotope-geochemical studies have not yet been carried out. Therefore, one cannot identify the sources or provenance of these sedimentary rocks. To fill this gap, we conducted petrochemical (120 samples), geochemical (30 samples), and Sm–Nd isotope–geochemical (15 samples) studies of terrigenous rocks of the Ladoga Group along the 45-km-long submeridional Lake Janisjarvi–Lake Ladoga profile. The results of this study are considered in this paper.